2014
DOI: 10.1056/nejmoa1214901
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Prolonged Co-trimoxazole in HIV-Infected Children in Africa

Abstract: Continuing co-trimoxazole prophylaxis after 96 weeks of ART was beneficial, as compared with stopping prophylaxis, with fewer hospitalizations for both malaria and infection not related to malaria. (Funded by the United Kingdom Medical Research Council and others; ARROW Current Controlled Trials number, ISRCTN24791884.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 35 publications
4
115
2
1
Order By: Relevance
“…It is likely that these additional benefits are related to antibacterial, antimalarial and anti‐inflammatory effects. The findings of this trial are therefore less likely to be of relevance in most European settings 30.…”
Section: Prophylaxis Against Opportunistic Infectionsmentioning
confidence: 84%
See 1 more Smart Citation
“…It is likely that these additional benefits are related to antibacterial, antimalarial and anti‐inflammatory effects. The findings of this trial are therefore less likely to be of relevance in most European settings 30.…”
Section: Prophylaxis Against Opportunistic Infectionsmentioning
confidence: 84%
“…This option is also therefore endorsed by these guidelines. Daily co‐trimoxazole prophylaxis may also be considered for children travelling to countries with a high prevalence of bacterial infections and/or malaria, irrespective of their CD4 count/percentage and current treatment status 6, 24, 30, 31. The use of co‐trimoxazole in this context may also have additional benefit as antimalarial prophylaxis 32, although specific malaria prophylaxis appropriate to the regions being visited should always be prescribed.…”
Section: Prophylaxis Against Opportunistic Infectionsmentioning
confidence: 99%
“…A recently published trial with HIV-infected children receiving long-term ART in sub-Saharan Africa comparing continuing versus stopping co-trimoxazole prophylaxis found that continued co-trimoxazole prophylaxis was beneficial, with fewer hospitalizations and diagnostically confirmed malaria cases (14). Interestingly, fewer cases of other infections and also fewer cases of TB occurred in the continued co-trimoxazole group (5/376 and 15/ 382 TB events in the continued versus stopped co-trimoxazole group, respectively; hazard ratio, 0.33 [95% CI, 0.12 to 0.91]; P ϭ 0.032).…”
Section: Discussionmentioning
confidence: 99%
“…28 Dangarembizi, dkk. 29 melaporkan bahwa terdapat 17% kejadian efek samping derajat 3 dan 4 pada kelompok yang dihentikan, sementara pada kelompok yang dilanjutkan kejadian efek samping derajat 3 dan 4 adalah 15% dengan rasio hazard 1,20 dan IK 95% 0,83-1,72; p=0,33. Efek samping yang dilaporkan tersebut adalah anemia dan netropenia.…”
Section: Efek Samping Profilaksis Primer Kotrimoksazolunclassified